2009
DOI: 10.22358/jafs/66437/2009
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on allele frequency at the <i>CSN1S2</i> locus and its relationship with milk parameters in the Sarda goat

Abstract: The aim of the study was to assess allele frequencies at the CSN1S2 locus in the Sarda goat and the effects of the genotype on milk composition. Two hundred twenty Sarda goats from 20 farms were selected. Individual blood and milk samples were collected during the middle of lactation and daily milk yield was registered. Fat, protein and lactose percentage, freezing point, pH, somatic cell count and total mesophilic count were measured. DNA was analysed with different methods based on PCR. Allele frequencies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…In this study, A, B, C, and F alleles were observed in the South African dairy goat populations, with the A allele occurring at the highest frequency, followed by the F allele. Similar frequencies for allele A and F were reported in Italian (Vacca et al, 2009), Sicilian (Gigli et al, 2008;Palmeri et al, 2014), and West African goat breeds (Caroli et al, 2006;Caroli et al, 2007). The high occurrence of allele A in the South African goat population may be attributed to the A allele being considered almost fixed in the majority of Western breeds (Selvaggi & Tufarelli, 2011).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, A, B, C, and F alleles were observed in the South African dairy goat populations, with the A allele occurring at the highest frequency, followed by the F allele. Similar frequencies for allele A and F were reported in Italian (Vacca et al, 2009), Sicilian (Gigli et al, 2008;Palmeri et al, 2014), and West African goat breeds (Caroli et al, 2006;Caroli et al, 2007). The high occurrence of allele A in the South African goat population may be attributed to the A allele being considered almost fixed in the majority of Western breeds (Selvaggi & Tufarelli, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…The Toggenburg population had a frequency of 0.225 for CSN1S2 B, which was higher than the low frequencies of between 0.005 and 0.051 reported by Caroli et al (2006;, Gigli et al (2008) and Vacca et al (2009;2014). Furthermore, the AB genotype was observed in all the populations except for the Saanen population.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The CSN1S2 B and C alleles were characterized by Allele Specific-PCR (Vacca et al, 2009b). Since primer pair used in Allele Specific-PCR did not discriminate C and E alleles, C allele was assigned after CSN1S2 E allele identification which was obtained using primer pair by Chessa et al (2008) and restriction enzyme by Lagonigro et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…At CSN1S2 locus alleles B and C/E were detected by multiplex AS-PCR (Vacca et al, 2009). The allele E was identified by PCR-RFLP protocol of Lagonigro et al (2001) using primers by Chessa, Rignanese, Chiatti, et al (2008).…”
Section: Reagents Standards and Samplesmentioning
confidence: 99%